2022
DOI: 10.3390/jcm11133919
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Manipulated Virtual Kinematic Intervention in Individuals with Traumatic Stiff Shoulder: A Pilot Study

Abstract: Virtual reality enables the manipulation of a patient’s perception, providing additional motivation to real-time biofeedback exercises. We aimed to test the effect of manipulated virtual kinematic intervention on measures of active and passive range of motion (ROM), pain, and disability level in individuals with traumatic stiff shoulder. In a double-blinded study, patients with stiff shoulder following proximal humerus fracture and non-operative treatment were randomly divided into a non-manipulated feedback g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Despite the many advantages that VR is projected to bring to the field of shoulder rehabilitation, the validity and effectiveness of kinematic intervention in virtual environments for orthopedic rehabilitation have only been explored by a few studies [3,[27][28][29], none of which mention evaluating the performance of VR applications against pre-established criteria like clinical guidelines and/or staged ROM goals. Hence, the performed investigation compared the movements performed during different levels of the VR app against the gold-standard values using a motion capture system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the many advantages that VR is projected to bring to the field of shoulder rehabilitation, the validity and effectiveness of kinematic intervention in virtual environments for orthopedic rehabilitation have only been explored by a few studies [3,[27][28][29], none of which mention evaluating the performance of VR applications against pre-established criteria like clinical guidelines and/or staged ROM goals. Hence, the performed investigation compared the movements performed during different levels of the VR app against the gold-standard values using a motion capture system.…”
Section: Discussionmentioning
confidence: 99%
“…The growing impact of VR on shoulder rehabilitation is undeniable, as seen by the promising results of the present study, as well as the several new experimental trials working on the development of these VR applications. One double-blinded pilot study found that manipulated virtual real-time presentation of a subject's movements during shoulder exercises promoted greater active flexion ROM [3]. Another study investigated the influence of game features and practice type, task-oriented or imitation-oriented, on shoulder muscle activity [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations